Quality of life among people living with HIV in England and the Netherlands: a population-based study - Popping, Stephanie; Kall, Meaghan; Nichols, Brooke E.; Stempher, Evelien; Versteegh, Lisbeth; van de Vijver, David. A.M.C.; van Sighem, Ard; Versteegh, M.; Boucher, Charles; Delpech, Valerie; Verbon, Annelies (The Lancet regional health. Europe, 2021)
HIV is now considered a chronic condition, and people living with HIV, when treated, have a similar life expectancy as compared to the general population. Consequently, improving and ensuring a good health-related quality of life (HrQoL) among people living with HIV (people living with HIV) is increasingly important and has risen on the global agenda in recent years. A ‘fourth 90’ as 90% of people with viral load suppression have a good HrQoL should therefore be adopted alongside the other 90-90-90 targets. This study aims to report the progress on HrQoL as the ‘fourth 90’ and compare against the general population in the Netherlands and England. In the Netherlands, individuals attending the HIV outpatient clinic of a tertiary hospital were asked to complete the EQ-5D-5L from June 2016 until December 2018. In England, individuals attending one of 73 HIV outpatient clinics were randomly sampled to complete the Positive Voices survey, which included the EQ-5D-5L, from January to September 2017. HrQoL scores were combined with demographic data and compared to general population data. The EQ-5D-5L was filled-out by 895 people living with HIV in the NL and 4,137 in England. HrQoLutility was 0·85 among Dutch and 0·83 among English people living with HIV. This equated to 98% and 94% of the general population HrQoLutility in the Netherlands and England, respectively. Of the EQ-5D domains, anxiety/depression was mostly affected, with one-third in Dutch (35%) and almost half (47%) of English people living with HIV reporting symptoms. This was higher compared to their respective general populations (21% NL and 31% England). Overall, HrQoLutility for people living with HIV was high in both countries and highly comparable to the general populations Nevertheless, there should be an increased focus on anxiety and depression in the people living with HIV population The EQ-5D-5L proved an easy HrQoL measurement tool and identified areas for improvement by social and behavioural interventions. The study received funding (unrestricted grants) from: Gilead sciences, ViiV Healthcare, MSD, and Jansen pharmaceuticals.